Efficient and Equitable Urban Construction Tax Policy in Tehran's District 5: A VAR-Based Institutional Analysis - Alavi, Sayyed Ali; Rasouli, Majid; Yousefi, Mehdi (Journal of Posthumanism, 2025)
Infrastructure and public services. However, improperly designed tax policies can discourage private investment and contribute to unsustainable urban development. This study investigates the causal relationship between various municipal charges—including building permit fees, renovation taxes, and construction levies—and residential construction activity in District 5 of Tehran, one of the city’s fastest-growing urban areas. Employing a Vector Autoregressive (VAR) model and using quarterly data from 2011 to 2024, the study reveals significant negative effects of increased municipal charges on construction volumes. Specifically, shocks to construction and renovation fees lead to measurable declines in residential building activity. The analysis further suggests bidirectional interactions between permit charges and construction output, indicating a potential feedback loop. Findings highlight the need for a more flexible, context-sensitive taxation policy that avoids deterring development while ensuring sustainable municipal revenue. Policy recommendations include differentiated tax rates based on project type, incentives for green construction, and transparent online platforms for fee calculation and payment.